An External Quality Assessment Of Haematology Laboratories-A Ghanaian Experience (Journal of Science and Technology, 2016)
Developed countries have guaranteed the quality of clinical laboratories through quality assurance programmes. However, these programmes have not received the needed attention in Ghanaian haematology laboratories, as is the case in many developing countries where visual counting of blood cells are the usual procedures. To assess the level of analytical quality of haematology laboratories in the Ashanti region of Ghana, form of an external quality assessment scheme was undertaken. The survey covered twelve haematology laboratories in both the public and the private sectors. Control blood samples were sent to the laboratories to be analyzed. The study, which lasted for five months,covered such routine haematological parameters as Hb, PCV, Total WBC and platelets. The results from these laboratories were compared to that of an automated cell counter using the Cell-Dyn 3700 (Abbot Diagnostic Division, USA). About 80% of the laboratories studied which were using the manual counting, achieved the medically accepted analytical performance for all the parameters except platelets, where the percentage of the laboratories dropped to about 70%. The study has established the need for a continuous internal and external quality assessment in haematology. Such practice together with continuous education of laboratory personnel and the provision of automated instrumentswill help to achieve optimum laboratory quality needed for proper health care delivery in thecountry.